Learning Media Application Development Web-Based Health Sports Physical Education in Class 2 MTs Guppi Sukomoro - Suhanti, Ira Astonia; Iyakrus, Iyakrus; Destriana, Destriana (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This research aims to produce a product in the form of web-based PJOK learning media, and to determine the level of feasibility of the learning media. This type of research is research and development (R&D). Development procedures include potential and problems, data collection, product design, design validation, design revision, product testing, product revision, usage trials, product revision, and mass production. The product is web-based learning media for PJOK subjects which has been declared suitable as learning media based on validation results from material experts with an average score of 3.58 in the "valid" category, media experts with an average of 3.47 in the "valid" category ”, small group field trials obtained an average of 4.96 in the “very good” category, large scale field trials obtained an average of 4.90 in the “very good” category. The test items obtained an average of 0.72. Web-based PJOK learning media is proven by increasing student learning outcomes based on data from pretest and posttest evaluation results.